Efektifitas “Plasma” Schoology dalam Meningkatkan Self Regulated Learning (SRL) Siswa Kelas XII IPA SMAN 1 Gedongtataan - Aswin Saputra (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
The use of virtual classrooms in the learning process is a strategic step to create a flexible learning experience, accessible anytime and anywhere. Schoology's "Plasma" as a virtual classroom platform offers various digital learning features that enable students to develop Self-Regulated Learning (SRL). Through access to materials, discussions, and other digital learning resources, students are encouraged to be more active, independent, and able to plan, monitor, and evaluate their own learning process. SRL is an important internal factor that plays a role in learning success, because it encourages students to realize their learning needs without relying on direct direction from the teacher. This study is a classroom action research conducted by mathematics teachers at SMA Negeri 1 Gedongtataan, Pesawaran, Lampung, with 30 students of grade XII IPA 1 in the 2022/2023 academic year. Data were collected through questionnaires, observations, and interviews, then analyzed using descriptive statistics. The results showed that the use of Schoology's virtual classroom significantly improved students' SRL. The comparison of the average SRL scores in Cycle I and Cycle II, 2.7 and 3.2, respectively, indicates a consistent increase. This finding confirms that the integration of Schoology's virtual classroom is effective in enhancing students' learning independence at the secondary education level.